Prevalence of cancer and the benign call rate of afirma gene classifier in 18F‐Fluorodeoxyglucose positron emission tomography positive cytologically indeterminate thyroid nodules. (15th January 2021) - Endo, Mayumi; Sipos, Jennifer A.; Ringel, Matthew D.; Porter, Kyle; Nagaraja, Haikady N.; Phay, John E.; Shirley, Lawrence A.; Long, Clarine; Wright, Chadwick L.; Roll, Katie; Nabhan, Fadi A.
Abstract: Background: 18 F‐Fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) positive (PET+) cytologically indeterminate thyroid nodules (ITNs) have variable cancer risk in the literature. The benign call rate (BCR) of Afirma Gene Classifier (Gene Expression Classifier, GEC, or Genome Sequence Classifier, GSC) in (PET +) ITNs is unknown. Methods: This is a retrospective study at our institution of all patients with (PET+) ITNs (Bethesda III/IV) from 1 January 2010 to 21 May 2019 who underwent Afirma testing and/or surgery or repeat FNA with benign cytology. Results: Forty‐five ( PET+) ITNs were identified: 31 Afirma‐tested (GEC = 20, GSC = 11) and 14 either underwent surgery ( n  = 13) or repeat FNA (Benign cytology) ( n  = 1) without Afirma. The prevalence of cancer and noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) including only resected nodules and ITN with repeat benign FNA ( n  = 33) was 36.4% (12/33). Excluding all Afirma "suspicious" non‐resected ITNs and assuming all Afirma "benign" ITNs were truly benign, that prevalence was 28.6% (12/42). The BCR with GSC was 64% compared to 25% with GEC ( p  = 0.056). Combining GSC/GEC‐tested ITNs, the BCR was higher in ITNs demonstrating low/very low‐risk sonographic pattern by the American Thyroid Association (ATA) classification and ITNs scoring <4 by the American College of Radiology Thyroid Imaging, Reporting and Data System (ACR‐TI‐RADS) than ITNs with higher sonographic pattern/score ( p  = 0.025). Conclusions: The prevalence of cancer/NIFTP in (PET+) ITNs was 28.6–36.4% depending on the method of calculation. The BCR of Afirma GSC was 64%. Combining Afirma GEC/GSC‐tested ITNs, BCR was higher in ITNs with a lower risk sonographic pattern. Abstract : In this study, the prevalence of cancer and noninvasive follicular thyroid neoplasm with papillary‐like nuclear features in PET positive cytologically indeterminate thyroid nodules was 28.6–36.4% depending on the method of calculation. The benign call rate of Afirma GSC in these nodules was 64%. When combining Afirma GEC/GSC tested PET positive cytologically indeterminate thyroid nodules, the benign call rate was higher in nodules with a lower risk sonographic pattern.